The financial aspect of non-governmental organizations - case of Slovenia - Stanimirović, Tatjana (Central European Public Administration Review, 2021)
Purpose: As part of the third sector, non-governmental organisations have become an important factor in the public life of modern countries. This emerging wave can be noticed especially in South-East Europe during the transition period. In this context, the aim of the paper is to analyse the financial aspect of the NGOs’ business model, exposing cumulative data for Slovenia for the past eleven years. Design/Methodology/Approach: Based on the financial data obtained, the paper reveals the structure of financing of Slovenian NGOs in total amounts, as well as the trends of change for specific categories. Using descriptive methodology, it focuses mainly on the dissection of funds acquired from public finances. Findings: The results show that in 2019, Slovenian NGOs recorded almost EUR 1 billion of total revenues after increasing rapidly over the entire period under consideration (2009–2019). As far as the funds acquired from public finances are concerned, the amounts were higher at governmental level where funds are provided by ministries than at the local level that receives funds from municipalities, which had not been the case before 2019. Practical implications: The challenge for further research is an in-depth study of Slovenian NGOs’ financial strategy focusing on bidirectional financing as well as an analysis of public services currently provided by NGOs compared to services needed in the future. Originality/value: The paper is a pioneer attempt to analyse the financing of NGOs in Slovenia.
Keywords: financing; financiranje; javna sredstva; nevladne organizacije; non-governmental organizations (NGO); private funds; public funds; zasebna sredstva